Cognition-associated gray matter volume alterations in long-COVID show sex-specific patterns - Toepffer, Antonia; Früh, Marlene; Rocktäschel, Tonia; Ballez, Johanna; Troll, Marie; Güllmar, Daniel; Finke, Kathrin; Reuken, Philipp A.; Stallmach, Andreas; Vonderlind, Sabine; Dunay, Ildiko Rita; Gaser, Christian; et al. (Frontiers in Psychiatry, 2025)
IntroductionThe long-term effects of the coronavirus disease 2019 (COVID-19) are a major concern in today’s society, with cognitive impairment being an important manifestation. Notably, men and women exhibit differences in disease progression and the prevalence of long-COVID. This study aims to investigate sex differences in cognitively impaired long-COVID individuals and their potential association with alterations in gray matter volume (GMV).MethodsWe conducted MRI at 3 Tesla to investigate brain structural correlates of cognitive impairment in long-COVID patients using voxel-based morphometry (VBM) and compared these patients to a healthy control (HC) group (n=30, female=13, male=17). Long-COVID patients underwent scanning and neuropsychiatric assessment on average 9.9 months after their acute and mostly mild COVID-19 infection. Based on Montreal Cognitive Assessment (MoCA) scores, they were classified into two groups: the PCn group, showing preserved cognitive function with MoCA scores of 26 or higher (n=36, female=23, male=13), and the PCcog group, characterized by cognitive impairment with MoCA scores below 26 (n=28, female=15, male=13). Subsequent analyses were performed separately for males and females to investigate sex-specific brain structural correlates of cognitive impairment.ResultsOur analysis revealed significant GMV alterations in long-COVID patients across various brain regions, encompassing both shared and sex-specific regional changes. In females, these alterations were more restricted, affecting anterior frontal, limbic, and diencephalic regions. In males, GMV alterations were more widespread, involving neocortical regions such as the parietal, occipital, and motor cortices, and were characterized by a greater number of affected clusters.DiscussionOur findings demonstrate GMV alterations in both men and women with cognitive impairment, exhibiting sex-specific differences in affected regions. These differences suggest potentially distinct underlying mechanisms, highlighting the need for further research into their functional implications and relevance for personalized treatment strategies.